2022
DOI: 10.3390/jcm11061550
|View full text |Cite
|
Sign up to set email alerts
|

Trans-Spinal Electrical Stimulation Therapy for Functional Rehabilitation after Spinal Cord Injury: Review

Abstract: Spinal cord injury (SCI) is one of the most debilitating injuries in the world. Complications after SCI, such as respiratory issues, bowel/bladder incontinency, pressure ulcers, autonomic dysreflexia, spasticity, pain, etc., lead to immense suffering, a remarkable reduction in life expectancy, and even premature death. Traditional rehabilitations for people with SCI are often insignificant or ineffective due to the severity and complexity of the injury. However, the recent development of noninvasive electrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 141 publications
0
26
0
Order By: Relevance
“…Electroceutical are categorized as therapeutics targeting neural circuits of the internal organs 141 . Treatment examples include vagus nerve stimulation 142 , spinal cord stimulation 143 , cochlear 143 and retinal 144 stimulation through biocompatible implants. This approach is extended in targeting chronic lung disorders 145 , hypertension 146 , diabetes and gastrointestinal diseases 147 .…”
Section: Nanotechnology and Theranosticsmentioning
confidence: 99%
“…Electroceutical are categorized as therapeutics targeting neural circuits of the internal organs 141 . Treatment examples include vagus nerve stimulation 142 , spinal cord stimulation 143 , cochlear 143 and retinal 144 stimulation through biocompatible implants. This approach is extended in targeting chronic lung disorders 145 , hypertension 146 , diabetes and gastrointestinal diseases 147 .…”
Section: Nanotechnology and Theranosticsmentioning
confidence: 99%
“…It has been reported that the safety limits and the patient's comfort level have a direct correlation to charge injection density (C/cm 2 ), electrode material, and stimulation protocols [5], [13], [14]. These factors combined with individual variances between patients require the current threshold to be programmable.…”
Section: System Programmabilitymentioning
confidence: 99%
“…1b, resulting in over-current stimulation. It has been reported in the literature that over-current stimulation leads to discomfort, pain, or even tissue damage [5], [6]. Therefore, a safety mechanism is an indispensable functional block in a muscular stimulator to cope with over-current stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…2 Recent studies found that, in case of a disruption of the connection between the brain and the spinal cord, resulting from an injury or disease, motor tasks can be enabled by TESCS to the cervical and/or lumbosacral segments of the spinal cord. 7,8 Modi cation of spasticity by tonic TESCS was also demonstrated in individuals with spinal cord injury. 9 In a recent study, it has also been demonstrated that TESCS can induce rhythmic activities of legs in robotic orthosis driven body-weight support system in upright position in people with complete spinal cord injury.…”
Section: Introductionmentioning
confidence: 99%